RESPON ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR DARING PADA MASA PANDEMI COVID-19: Belajar Daring Pada Masa Pandemi Covid-19 - indra joni; Syahri Ramadhan; Yundri Akhyar; Ayu Purnamasari; Parlindungan Simbolon (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the response of parents in accompanying children to learn online during the Covid-19 pandemic at SDN 013 Tandun. This type of research uses a survey design. The research was conducted at SDN 013 Tandun, Rokan Hulu Regency by taking a random sample in order to obtain 60 parents. Based on a questionnaire that has been distributed to the parents of students, on average parents have graduated from high school, to support the online process parents have an android cellphone or laptop, but there are problems with unstable network problems, there are parents who cannot use an android cellphone. or laptops, there are parents who cannot understand the subject matter provided by the teacher, some are unable to help children complete assignments due to busy work and limited knowledge, many students are not motivated to learn online and many parents find it difficult to be a teacher because the child is not want to be organized and play a lot. This shows that parents experienced various obstacles in accompanying children to learn online during the pandemic Covid-19.